The The Influence of Work-Life Balance and Job Embeddedness on Turnover Intention Among Generation Z Employees Through Job Satisfaction in Semarang City - Luluk Salma Ida; Purwanto, Edy; Fajri, Annisa (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of work-life balance and job embeddedness on turnover intention among Generation Z employees in Semarang City, with job satisfaction as a mediating variable. Using a quantitative survey and PLS-SEM analysis, the results show that job embeddedness positively and significantly affects job satisfaction, while work-life balance does not. However, work-life balance, job embeddedness, and job satisfaction significantly reduce turnover intention. Job satisfaction does not mediate the effect of work-life balance on turnover intention but does mediate the relationship between job embeddedness and turnover intention. Strengthening employee embeddedness is essential to lowering turnover intention among Generation Z.